Kedudukan Media Massa Dalam Gerakan Sosial Perempuan Di Indonesia : Analisis Terhadap Beberapa Kasus Trending Topic Di Tahun 2021 - Alfan Bachtiar; Udi Rusadi (Brand Communication, 2022)
Abstract: The interaction relationship between social movements and mass media is not a simple thing but very complex to just define. Social movements need means to make their voices heard and their activities visible. So to show the wider community, social movements need mass media. As for the media, they have different ways of dealing with social movements because of the different orientations between the two. Social movements aim to make the public believe in their ideology while the media is oriented towards economic gain. By taking 3 (three) cases that became trending topics in the 4th quarter of 2021, this paper analyzes the interaction relationship between social movements and mass media in these 3 cases. The theoretical basis used comes from the thoughts of Wim van de Donk, Brian D. Loader, Paul G. Nixon, and Dieter Rucht. The results of the study show that most social movements oriented to the protection of women have their own independent media. However, social movements also indirectly managed to attract the attention of the established media. This is because these movements have been able to attract the attention of all Indonesian people. If this relationship becomes balanced then it will be beneficial for both. Social movements will be able to spread ideas widely with the help of established media. The mass media will also achieve its goals in service and economic benefits.